Social Protection for the Vulnerable: Appraisal of Cash Transfer Programme on the Welfare of Beneficiaries in Ekiti State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2023)
Social protection programme are structured as a pro-poor all-inclusive policy designed to alleviate poverty in many countries of the world including Nigeria, owing to the ongoing uncertainties in the global economy. This study examines the rationale for and framework of Social Protection Policy, particularly cash transfer on the socio-economic status of beneficiaries in Ekiti State. The study further examines the challenges confronting the implementation of the scheme. The study adopts both quantitative and qualitative methods in its investigation. Data for the study were gathered from primary sources through questionnaire, in-depth interview and focus group discussions (FGDs) while secondary data were sourced from relevant text, internet sources and official publication on National Cash Transfer. Table, percentage and content analytical methods were employed for data analysis. The study reveals that cash transfer programme has really improved the socio-economic status of beneficiaries, especially at the grassroots in Ekiti State. This paper concludes that if the scheme capture the real poor vulnerable in Ekiti State and monthly stipends are paid regularly and promptly, it is capable of reducing poverty and improves economic capacity building in the state.